(untitled) (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة 26 مريضاًَ تراوحت أعمارهم بين 3 أشهر – 12 سنة، قبلوا في قسم الأطفال مشفى الأسد الجامعي باللاذقية خلال عام واحد ( 2005 – 2006 ) بتظاهرات سريرية مختلفة، وتبين لديهم نقص صفيحات، وتم وضع تشخيص نقص الصفيحات الأساسي بعد بزل النقي. تم تقسيم المرضى إلى مجموعتين: • المجموعة (1): مجموعة الأمينوغلوبولين الوريدي وضمت 9 مرضى. • المجموعة(2): مجموعة البريدنزلون وضمت 17 مريضاً. تم تطبيق كل خطة علاجية مع تحديد عدد الصفيحات عند التشخيص، وفي الأيام: 2-3-5-7-14-30- 90- 180 من العلاج. بلغت نسبة المرضى الذين تجاوز لديهم تعداد الصفيحات 20 ألف/مم3 في اليوم الثاني من تطبيق العلاج 88.8% (8 مرضى) في المجموعة الأولى، بينما بلغت 23.5% (5 مرضى) في المجموعة الثانية. كان متوسط عدد الأيام التي استغرقها عدد الصفيحات للعودة > 100 ألف/مم3، (4.2) يوماً للمجموعة الأولى و(21) يوماً للمجموعة الثانية. تبين وجود اختلاف جوهري في سرعة الاستجابة على العلاج لصالح الأمينوغلوبولين مع نسبة شفاء أعلى من البريدنزولون. This study included 26 patients aged between 3 months – 12 years who were hospitalized in Pediatrics Department at AL-ASSAD University Hospital in Latakia in one year (2005-2006) with different clinical features. It proved that they had thrombocytopenia, using the diagnosis of idiopathic thrombocytopenic purpura by marrow aspiration. The patients were divided into two groups: Group (1): intravenous immunoglobulin; it included 9 patients. Group (2): prednisolon; it included 17 patients. Both methods of treatment were employed, and platelet counts of the patients were determined at diagnosis, and at 2,3,5,7,14,30,90, and180 days of treatment. The percentages of patients with platelet counts above 20,000/ml on the 2nd day of the treatment were 88.8% (8 patients) in the first group, and 23.5% (5 patients) in the second group. The mean time for achievement of platelet counts above 100,000/ml was (4.2) days for the first group, and (21) days for the second one. There were significant differences in response to treatment in favor of immunoglobulin with a higher recovery percentage than prednisolon.